2013
DOI: 10.3748/wjg.v19.i43.7751
|View full text |Cite
|
Sign up to set email alerts
|

Transanal natural orifice specimen extraction for laparoscopic anterior resection in rectal cancer

Abstract: Transanal NOSE for total laparoscopic low/ultralow anterior resection is feasible, safe and oncologically sound. Further studies with long-term outcomes are needed to explore its potential advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…All patients were commenced on ambulatory physiotherapy and tolerated oral intake by the first post-operative day, and all met discharge criteria by the third post-operative day. There were no incidences of anastomotic leaks, fissures, or deterioration of anal continence as measured by Wexner scores immediately post-operatively and during outpatient review over a median follow-up of 9 months (range, [8][9][10][11]. The two oldest patients had preoperative Wexner scores of '1', remaining unchanged postoperatively.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…All patients were commenced on ambulatory physiotherapy and tolerated oral intake by the first post-operative day, and all met discharge criteria by the third post-operative day. There were no incidences of anastomotic leaks, fissures, or deterioration of anal continence as measured by Wexner scores immediately post-operatively and during outpatient review over a median follow-up of 9 months (range, [8][9][10][11]. The two oldest patients had preoperative Wexner scores of '1', remaining unchanged postoperatively.…”
Section: Resultsmentioning
confidence: 91%
“…1,7,8 Either method has its shortcomings and limitations. We are partial to the transanal technique as it provides a consistent anatomical route for extraction independent of gender, especially as most of our patients are male.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid direct contact between the specimen and natural orifice the transluminal endoscopic operation port was used. Studies had emerged sustaining the efficacy and safety of this method (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have demonstrated that a D3 lymphadenectomy contributes to reducing both the local recurrence and distant metastasis and ameliorates the survival of patients with rectal cancer (5) .Furthermore, the laparoscopic approach results in a surgery that is, to a large extent, minimally invasive (14) . With the amplification effect of the laparoscope, the D3 lymphadenectomy achieves a thorough dissection of the involved lymph nodes and prevents distant metastasis and recurrence of the tumor.…”
Section: Discussionmentioning
confidence: 99%